Deep Learning-Based Daily Activity Storybook for Early Childhood Literacy Skills - Nur Alim Amri; Nurhidayat Nurhidayat; Abdul Muhsin; Abdul Hakim; Farida Febrianti (Ihya Ulum: Early Childhood Education Journal, 2026)
This study aims to examine the effectiveness of a deep learning–based daily activity storybook in enhancing early literacy skills among children aged 5–6 years. Employing a quantitative approach with a pre-experimental one-group pretest–posttest design, the research involved 22 children selected through purposive sampling. Data were collected using a validated and reliable literacy observation sheet (Aiken’s V = 0.84–0.95; a = 0.91; ICC = 0.84) measuring children’s ability to comprehend symbols, use vocabulary, and express ideas meaningfully. Statistical analysis using the Paired Sample t-test revealed a significant difference between pretest (M = 52.14, SD = 4.38) and posttest (M = 74.27, SD = 5.16) scores, t (21) = 13.42, p < 0.001, with a very large effect size (Cohen’s d = 2.86). The findings demonstrate that integrating deep learning principles into contextual storybooks substantially improves children’s functional and expressive literacy. The study’s novelty lies in combining literacy, communication, and experiential learning through a child-centered storytelling model. Practically, it offers teachers an innovative pedagogical tool aligned with the Merdeka Curriculum, fostering joyful and meaningful learning. This research contributes to strengthening the theoretical and practical foundation of deep learning–based literacy education in early childhood contexts.